At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To find [tex]\( f(x) \)[/tex] when [tex]\( x = 3 \)[/tex] for the function [tex]\( f(x) = 2x^2 + 1 \)[/tex], follow these steps:
1. Substitute the value of [tex]\( x \)[/tex] into the function:
[tex]\[ x = 3 \][/tex]
2. Write down the function:
[tex]\[ f(x) = 2x^2 + 1 \][/tex]
3. Substitute [tex]\( x = 3 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(3) = 2(3^2) + 1 \][/tex]
4. Calculate the square of 3:
[tex]\[ 3^2 = 9 \][/tex]
5. Multiply the result by 2:
[tex]\[ 2 \cdot 9 = 18 \][/tex]
6. Add 1 to the result:
[tex]\[ 18 + 1 = 19 \][/tex]
Therefore, [tex]\( f(x) \)[/tex] when [tex]\( x = 3 \)[/tex] is [tex]\( 19 \)[/tex].
Thus, the correct answer is:
[tex]\[ \boxed{19} \][/tex]
1. Substitute the value of [tex]\( x \)[/tex] into the function:
[tex]\[ x = 3 \][/tex]
2. Write down the function:
[tex]\[ f(x) = 2x^2 + 1 \][/tex]
3. Substitute [tex]\( x = 3 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(3) = 2(3^2) + 1 \][/tex]
4. Calculate the square of 3:
[tex]\[ 3^2 = 9 \][/tex]
5. Multiply the result by 2:
[tex]\[ 2 \cdot 9 = 18 \][/tex]
6. Add 1 to the result:
[tex]\[ 18 + 1 = 19 \][/tex]
Therefore, [tex]\( f(x) \)[/tex] when [tex]\( x = 3 \)[/tex] is [tex]\( 19 \)[/tex].
Thus, the correct answer is:
[tex]\[ \boxed{19} \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.